2018
DOI: 10.1080/10803548.2018.1489993
|View full text |Cite
|
Sign up to set email alerts
|

Promoting evidence-based practice – perceived knowledge, behaviours and attitudes of Polish nurses: a cross-sectional validation study

Abstract: Study findings highlight the importance of further supplementation of knowledge about EBP. The difficulties in using EBP in clinical practice are objective and require changes in the Polish system of nursing care. Additionally, life-long updating knowledge in the area of EBP by participation in various forms of postgraduate education can produce improvements in the knowledge, behaviours and attitudes of nurses in creating a positive EBP profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 18 publications
3
38
0
Order By: Relevance
“…We found no certain associations between type of understanding and length of experience in clinical practice. However, participants with higher academic degrees were more likely to have the deeper understanding, supporting the findings of Belowska et al (), who found that nurses with a master's degree understand terms related to EBN and are able to explain them to colleagues. This is an important finding that needs further study.…”
Section: Discussionsupporting
confidence: 82%
“…We found no certain associations between type of understanding and length of experience in clinical practice. However, participants with higher academic degrees were more likely to have the deeper understanding, supporting the findings of Belowska et al (), who found that nurses with a master's degree understand terms related to EBN and are able to explain them to colleagues. This is an important finding that needs further study.…”
Section: Discussionsupporting
confidence: 82%
“…The educational level of the nurses was one of the variables associated with EBP competency, and the analysis according to the dimensions and items of the EBP‐COQ‐Prof© allowed us to obtain interesting findings. In first place, as already pointed out in previous studies, the higher the postgraduate training, the greater the level of knowledge, skills and EBP utilization (Belowska et al., 2018; Melnyk et al., 2018). Our findings also allowed us to assess the behaviour at the global level, as well as according to the dimensions of EBP competency, placing the bachelor's degree nurses in lower percentiles and T ‐scores, which gradually increased following a master's, clinical nurse specialist and PhD path.…”
Section: Discussionmentioning
confidence: 57%
“…This is a national study for measuring EBP competency, with the largest sample of nurses until the present (Saunders & Vehviläinen‐Julkunen, 2016; Ubbink et al., 2013). The sociodemographic and professional profile of the participants coincided with the Spanish nurses who work in public health centres (Ministerio de Sanidad, 2019), and was similar to other countries (Belowska et al., 2018; Melnyk et al., 2018). It should be highlighted that the sample had a high proportion of nurses with postgraduate degrees (master's and PhD), higher than previous studies conducted in Spain and in other countries (Melnyk et al., 2018; Patelarou et al., 2017; de Pedro‐Gómez et al., 2011; Solís‐Muñoz, 2015).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In this study, RU is defined as a process involving acquisition, critical reading (including evaluation) and application of research knowledge [4,6]. The translation of research knowledge into clinical nursing practice, however, is often hampered, primarily due to nurses' lacking competence for RU [7,8].…”
Section: Introductionmentioning
confidence: 99%